1998
DOI: 10.1111/1467-937x.00059
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Neighbours

Abstract: When payoffs from different actions are unknown, agents use their own past experience as well as the experience of their neighbours to guide their decision making. In this paper, we develop a general framework to study the relationship between the structure of these neighbourhoods and the process of social learning.We show that, in a connected society, local learning ensures that all agents obtain the same payoffs in the long run. Thus, if actions have different payoffs, then all agents choose the same action,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
444
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 688 publications
(465 citation statements)
references
References 22 publications
15
444
0
6
Order By: Relevance
“…Social network structure can begin to play more of a role once agents either repeatedly take actions or repeatedly communicate with each other. A variation on the above model was investigated by Bala and Goyal (1998) and can be described as follows. Instead of taking actions just once, each agent takes an action at every date.…”
Section: Learningmentioning
confidence: 99%
“…Social network structure can begin to play more of a role once agents either repeatedly take actions or repeatedly communicate with each other. A variation on the above model was investigated by Bala and Goyal (1998) and can be described as follows. Instead of taking actions just once, each agent takes an action at every date.…”
Section: Learningmentioning
confidence: 99%
“…When social influence leads to correlated errors, both independence and diversity are reduced, which has been argued to compromise the reliability of the group judgment (9,(11)(12)(13)(14)(15)(16)(17)(18). In direct contrast with these results, however, theoretical models of social learning (19-21) have suggested that the effects of social influence on collective decisions vary based on the structure of the interaction network, predicting that, under the right conditions, social learning can lead a group's median judgment to improve (20)(21)(22)(23)(24).This prediction derives from the assumption that, when people learn about the beliefs of others, they revise their own beliefs to become more similar to their social referents (11, 12, 25, 26). Following the DeGroot model of social learning, this theory suggests that each individual's revisions are based on a weighted average of their own belief and the beliefs of their social referents (19).…”
mentioning
confidence: 99%
“…When social influence leads to correlated errors, both independence and diversity are reduced, which has been argued to compromise the reliability of the group judgment (9,(11)(12)(13)(14)(15)(16)(17)(18). In direct contrast with these results, however, theoretical models of social learning (19)(20)(21) have suggested that the effects of social influence on collective decisions vary based on the structure of the interaction network, predicting that, under the right conditions, social learning can lead a group's median judgment to improve (20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…This stands in contrast to models of social learning in which the agents have infinite memories where typically all of the agents settle on the same action (e.g. Bala and Goyal, 1998). These observations have welfare implications.…”
Section: Existencementioning
confidence: 85%